2018
DOI: 10.1038/s41467-018-06451-3
|View full text |Cite
|
Sign up to set email alerts
|

RIP2 filament formation is required for NOD2 dependent NF-κB signalling

Abstract: Activation of the innate immune pattern recognition receptor NOD2 by the bacterial muramyl-dipeptide peptidoglycan fragment triggers recruitment of the downstream adaptor kinase RIP2, eventually leading to NF-κB activation and proinflammatory cytokine production. Here we show that full-length RIP2 can form long filaments mediated by its caspase recruitment domain (CARD), in common with other innate immune adaptor proteins. We further show that the NOD2 tandem CARDs bind to one end of the RIP2 CARD filament, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
59
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 79 publications
(106 reference statements)
6
59
1
Order By: Relevance
“…Using this tool, we found that RIPosomes formed after NF-κB activation mediated by NOD1, which is contradictory to a direct role of these structures in NF-κB activation by NOD1/2, as recently proposed by others (Gong et al, 2018, Pellegrini et al, 2018. Activation of NF-κB responses by NOD1 and NOD2 is associated with membrane recruitment of NOD1 and NOD2 (Kufer, Kremmer et al, 2008, Lecine, Esmiol et al, 2007, Nakamura, Lill et al, 2014, Travassos, Carneiro et al, 2010.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Using this tool, we found that RIPosomes formed after NF-κB activation mediated by NOD1, which is contradictory to a direct role of these structures in NF-κB activation by NOD1/2, as recently proposed by others (Gong et al, 2018, Pellegrini et al, 2018. Activation of NF-κB responses by NOD1 and NOD2 is associated with membrane recruitment of NOD1 and NOD2 (Kufer, Kremmer et al, 2008, Lecine, Esmiol et al, 2007, Nakamura, Lill et al, 2014, Travassos, Carneiro et al, 2010.…”
Section: Discussionmentioning
confidence: 61%
“…The interaction of NOD1 and NOD2 with RIPK2 is mediated by heterotypic CARD:CARD interactions, involving residues in the exposed surfaces of the CARD domains of RIPK2 and NOD1/2 (Maharana, Pradhan et al, 2017, Manon, Favier et al, 2007, Mayle, Boyle et al, 2014. In vitro, this can result in stable rope-like structures, which were recently proposed to be platforms for subsequent NF-κB activation (Gong, Long et al, 2018, Pellegrini, Desfosses et al, 2018.…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies, higher order intracellular signalling platforms consisting of RIPK2 and NOD receptors were described [36,57,58]. In particular, inhibition of XIAP by either siRNA or by SMAC mimetic compounds led to RIPK2-containing speck-like structures in cells, termed Riposomes [36].…”
Section: Discussionmentioning
confidence: 99%
“…Upon binding to their respective PG metabolites, both Nod1 and Nod2 are believed to shift from an auto‐inhibited form to an active conformation that then can self‐oligomerise (Figure c) . The oligomeric Nod complexes then recruit receptor interacting serine/threonine kinase 2 (RIPK2) via CARD‐CARD interactions . In turn, the Nod/RIPK2 complex activates mitogen‐activated protein kinase (MAPK), nuclear factor kappa‐light‐chain enhancer of activated B cells (NF‐κB) and interferon transcription factor (IRF) pathways, which promotes the transcription of proinflammatory cytokines, antimicrobial peptides (AMPs) and type I interferon genes .…”
Section: Host Recognition Of Pg Metabolitesmentioning
confidence: 99%
“…[14][15][16] The oligomeric Nod complexes then recruit receptor interacting serine/threonine kinase 2 (RIPK2) via CARD-CARD interactions. 32,33 In turn, the Nod/RIPK2 complex activates mitogenactivated protein kinase (MAPK), nuclear factor kappa-light-chain enhancer of activated B cells (NF-jB) and interferon transcription factor (IRF) pathways, which promotes the transcription of proinflammatory cytokines, antimicrobial peptides (AMPs) and type I interferon genes. [14][15][16] Complex formation, stability and signal transduction are tightly controlled through numerous other proteins reviewed elsewhere.…”
Section: Introductionmentioning
confidence: 99%